Audit Experience, Role Ambiguity, and Healthy Lifestyle on Auditor Performance with Spiritual Intelligence: Pengalaman Audit, Ambiguitas Peran, Gaya Hidup Sehat, dan Kinerja Auditor - Andari, Miranda Putrin; Hermawan, Sigit (Indonesian Journal of Law and Economics Review, 2024)
Background: Auditor performance is key to ensuring financial accuracy. Specific Background: Audit experience, role ambiguity, and healthy lifestyle influence performance, but the role of spiritual intelligence as a mediator is less studied. Knowledge Gap: The mediation effect of spiritual intelligence in auditor performance is underexplored. Aims: This study examines the effects of audit experience, role ambiguity, and healthy lifestyle on auditor performance, with spiritual intelligence as a mediator. Results: Based on Partial Least Square (PLS) analysis of 65 auditors, audit experience, role ambiguity, and healthy lifestyle significantly affect both spiritual intelligence and auditor performance (p < 0.05). Spiritual intelligence also mediates these effects (p < 0.05). Novelty: The study emphasizes spiritual intelligence as a key mediator. Implications: Enhancing spiritual intelligence could improve auditor performance, offering practical insights for professionals and researchers. Highlights : Audit experience, role ambiguity, and healthy lifestyle directly affect auditor performance. Spiritual intelligence mediates the relationship between these factors and performance. Enhancing spiritual intelligence may improve overall auditor performance. Keywords: Audit Experience, Role Ambiguity, Healthy Lifestyle, Spiritual Intelligence, Auditor Performance